2018
DOI: 10.20882/adicciones.920
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo y validación de la versión corta del cuestionario sobre expectativas de los efectos del alcohol (EQ-SF)

Abstract: Resumen Abstract original adicciones vol. 30, nº 4 · 2018Alcohol expectancies are proximal variables to alcohol use and misuse.In recent decades, different measures have been developed to assess this construct. One of the most frequently used and recommended instruments is the Expectancy Questionnaire (EQ; Leigh y Stacy, 1993).Our aim is to develop a short version of the EQ (EQ-SF) for suitable use in time-limited administrations. Two samples, adolescents (N = 514, 57.20% females) and adults (N = 548, 61.50% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…By drawing on a Ghanaian adolescent sample—a population on which there has been little alcohol research—the aim of this study was to assess whether the construct of alcohol expectancies as measured by the AEQ [27] is valid within this sample. Confirmatory factor analyses suggested that while the groupings of positive and negative expectancies were broadly similar to those in the original work [27] and other Western samples [70, 71], among a Ghanaian adolescent sample, responses formed a single ‘alcohol expectancy’ factor rather than related separate positive and negative factors. Furthermore, questions relating to alcohol's positive effects on tension reduction (expecting to feel less stressed) and negative physical effects (experiencing unpleasant physical effects and expecting to feel sick) produced inconsistent responses among Ghanaian adolescents, contrary to previous factor analyses of Western data [46].…”
Section: Discussionsupporting
confidence: 66%
“…By drawing on a Ghanaian adolescent sample—a population on which there has been little alcohol research—the aim of this study was to assess whether the construct of alcohol expectancies as measured by the AEQ [27] is valid within this sample. Confirmatory factor analyses suggested that while the groupings of positive and negative expectancies were broadly similar to those in the original work [27] and other Western samples [70, 71], among a Ghanaian adolescent sample, responses formed a single ‘alcohol expectancy’ factor rather than related separate positive and negative factors. Furthermore, questions relating to alcohol's positive effects on tension reduction (expecting to feel less stressed) and negative physical effects (experiencing unpleasant physical effects and expecting to feel sick) produced inconsistent responses among Ghanaian adolescents, contrary to previous factor analyses of Western data [46].…”
Section: Discussionsupporting
confidence: 66%
“…Finally, a reduction in the number of items (AUC analysis) followed by an EFA of the reduced set of items was used to obtain a more reliable factor solution for the scale. This strategy has been shown to be useful when attempting to obtain robust versions of a questionnaire and has additional advantages such as reducing the time required to complete the questionnaire (Mezquita et al, 2018). To minimize predictability loss due to item elimination, an AUC analysis was carried out to select the items to be included in a shortened version of the MC-OWBS (Koczkodaj et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to indicate the likelihood of experiencing the aforementioned consequences when consuming alcohol. The reliability of the Spanish version of the EQ-SF (25) was adequate, with Cronbach’s alpha values ranging between .77 and .93.…”
Section: Methodsmentioning
confidence: 98%
“…The Spanish Short Form (EQ- SF) (25) of the Expectancies Questionnaire (14) comprises 24 items and employs a Likert response scale with 6 options, ranging from 0 (never) to 5 (always), to measure positive and negative expectancies. This scale is composed of 8 dimensions, 4 of which correspond to positive expectations (12 items): expectancies about social facilitation (Social Positive), positive affect potentiation (Fun Positive), sexual disinhibition (Sex Positive), and tension reduction (Tension Reduction).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation